2017
DOI: 10.1016/j.eururo.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Type A and B Molecular Subtypes in Metastatic Clear Cell Renal Cell Carcinoma: Tumor Heterogeneity and Aggressiveness

Abstract: Background Intratumor molecular heterogeneity has been reported for primary clear cell renal cell carcinoma (ccRCC) tumors; however, heterogeneity in metastatic ccRCC tumors has not been explored. Objective To evaluate intra- and intertumor molecular heterogeneity in resected metastatic ccRCC tumors. Design, setting, and participants We identified 111 patients who had tissue available from their primary tumor and at least one metastasis. ClearCode34 genes were analyzed for all tumors. Outcome measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 13 publications
4
46
0
Order By: Relevance
“…expression. Previous studies confirmed that the E2F pathway controlled tumor cell growth [33,34] Substantial heterogeneity was detected in ccRCC tissues in previous studies, and single biomarkers or biomarkers for predicting prognosis concluded from studies with fewer samples usually cannot meet the standard of efficacy and lead to treatment failure [37,38]. RNA-seq data from three studies were included in this study to overcome the heterogeneity, as identifying DEGs between primary and metastatic tissues would represent the prognosis better than target sequencing of single tissue.…”
Section: Discussionmentioning
confidence: 76%
“…expression. Previous studies confirmed that the E2F pathway controlled tumor cell growth [33,34] Substantial heterogeneity was detected in ccRCC tissues in previous studies, and single biomarkers or biomarkers for predicting prognosis concluded from studies with fewer samples usually cannot meet the standard of efficacy and lead to treatment failure [37,38]. RNA-seq data from three studies were included in this study to overcome the heterogeneity, as identifying DEGs between primary and metastatic tissues would represent the prognosis better than target sequencing of single tissue.…”
Section: Discussionmentioning
confidence: 76%
“…This can be achieved with the ultra-high DNA sequencing. However, apart from large catalogues of somatic mutations in cancer including ccRCC [ 14 , 15 ] provided by international sequencing projects like TCGA and ICGC, multiregional sequencing also revealed remarkable intra-tumor heterogeneity [ 16 18 , 20 ] Here, we provide evidence for considerable temporal molecular heterogeneity between therapy-naïve primary tumors and metastases developing under TKI. The mutational profiles provide insights into clonal evolution occuring during tumor progression under therapy: Molecular profiling revealed recurrent genomic alterations in genes frequently altered in ccRCC [ 14 ], including VHL , SETD2 , and BAP1.…”
Section: Discussionmentioning
confidence: 85%
“…On the molecular level, ccRCC is a heterogeneous tumor displaying a broad spectrum of genetic alterations [ 14 , 15 ]. Multiregion sequencing revealed intra-tumor heterogeneity of mRCC with wide subclonal diversity [ 16 18 ]. Here, we report the results of a pilot study (MORE, Molecular Renal Cancer Evolution) using whole-exome sequencing (WES) of primary and biopsy tissue samples from treatment-naïve patients at baseline and after TKI treatment respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial heterogeneity was detected in ccRCC tissues in previous studies, and single prognostic biomarker or the biomarkers concluded from studies with fewer samples usually cannot meet the standard of e cacy and lead to treatment failure [35,36]. RNA-seq data from three studies were included in this study to overcome the heterogeneity, as identifying DEGs between paired primary and metastatic tissues would represent the prognosis better than target sequencing on single tissue.…”
Section: Discussionmentioning
confidence: 99%